Control interno y Rentabilidad en empresas de alimentos y bebidas Loja: Estudio de caso: “Parrilladas el Fogón periodo 2018-2022 - Albito Cedillo, Johanna Maricela (2024)
Currently, internal control and profitability are of great importance to obtain successful results in economic profits. In this context, the present research work aims to determine the relationship between internal control and profitability in the food and beverage company Parrilladas el Fogón periods 2018-2022, being its mixed methodological approach, descriptive and correlational type, with a non-experimental design, inductive, deductive and mathematical methods were used, applying the internal control questionnaire, as well as financial and profitability indicators. The techniques and instruments used to collect information were direct observation, bibliographic review, the questionnaire and the narrative questionnaires with the respective procedures to complement the analysis. The results determined that when questionnaire is applied based on the five components, the internal control risk level is moderately high at 55.83% and a low confidence level of 44.17%. It is an unreliable control system due to some particularities or short comings of an operational nature, On the other hand, in the financial analysis an excess of liquidity was observed and through the profitability indicators significant variations were evidenced, especially in the last periods 2021 and 2022 regarding the Net Margin,Return on Assets (ROA) and Return on Equity (ROE), it is concluded that internal control is positively related to profitability - average with a value of 0.6326 according to Pearson's coefficient, the entity must apply controls that allow organizing and directing activities effectively and efficiently especially in the management area, establish strategic objectives aimed at the economic and productive growth of the company, which improve their profitability.